RESEARCH OF FORMING INFORMATION CULTURE FUTURE BACHELOR OF PHILOLOGY - Glushak, Oksana M. (Educological discourse, 2016)
In the article the research results of formation of information culture of the future bachelors of philology. Defined and analyzed levels of information culture of the future bachelors of philology - beginner, intermediate and high enough. The study determined that students in the experimental group indicators of levels of information culture very different from that of the levels of information culture of students in the control group. The students of the experimental group show high enough levels of information culture, indicating the feasibility of purposeful work on formation of information culture in Bachelor of Philology while studying disciplines of information and computer cycle.